1993
DOI: 10.1007/bf02368642
|View full text |Cite
|
Sign up to set email alerts
|

SENSOP: A derivative-free solver for nonlinear least squares with sensitivity scaling

Abstract: Nonlinear least squares optimization is used most often in fitting a complex model to a set of data. An ordinary nonlinear least squares optimizer assumes a constant variance for all the data points. This paper presents SENSOP, a weighted nonlinear least squares optimizer, which is designed for fitting a model to a set of data where the variance may or may not be constant. It uses a variant of the Levenberg-Marquardt method to calculate the direction and the length of the step change in the parameter vector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…In the classic case from Richardson (22), using calipers to measure the length of a coastline, he found that over a wide range, the relationship between the logarithm of the apparent measured length and the logarithm of the caliper length was linear, and slope gave a measure of the fractal dimension. Likewise, the variance in regional flows within the tissue of an organ was found by Bassingthwaighte (1) to exhibit a linear relationship between the log of the variance, or the standard deviation, SD, and the log of the size, m, of the observed unit: (8) from which the fractal dimension D is obtained from the slope of the log-log regression: (9) where m is the element size used to calculate SD, and m 0 is the arbitrarily chosen reference size, where "size" is the number of points aggregated together in a one-dimensional series, or a length over which an average is obtained, or the mass of a tissue sample in which a concentration is measured. The fractal dimension D = 2 − H, where H is the Hurst coefficient; we slide back and forth using D and H, but the advantage of H is that it gives a direct indication of the degree of smoothness or correlation which has the same meaning for signals of any Euclidean dimension, E. In general, H = E + 1 − D. A Hurst coefficient of 0.5 indicates a random noncorrelated signal (otherwise known as white noise) whether the signal is one-, two-, or three-dimensional.…”
Section: Dispersional Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…In the classic case from Richardson (22), using calipers to measure the length of a coastline, he found that over a wide range, the relationship between the logarithm of the apparent measured length and the logarithm of the caliper length was linear, and slope gave a measure of the fractal dimension. Likewise, the variance in regional flows within the tissue of an organ was found by Bassingthwaighte (1) to exhibit a linear relationship between the log of the variance, or the standard deviation, SD, and the log of the size, m, of the observed unit: (8) from which the fractal dimension D is obtained from the slope of the log-log regression: (9) where m is the element size used to calculate SD, and m 0 is the arbitrarily chosen reference size, where "size" is the number of points aggregated together in a one-dimensional series, or a length over which an average is obtained, or the mass of a tissue sample in which a concentration is measured. The fractal dimension D = 2 − H, where H is the Hurst coefficient; we slide back and forth using D and H, but the advantage of H is that it gives a direct indication of the degree of smoothness or correlation which has the same meaning for signals of any Euclidean dimension, E. In general, H = E + 1 − D. A Hurst coefficient of 0.5 indicates a random noncorrelated signal (otherwise known as white noise) whether the signal is one-, two-, or three-dimensional.…”
Section: Dispersional Analysismentioning
confidence: 91%
“…In our introductory paper, an application of dispersional analysis to the velocities of red blood cells in capillaries did give a straight-line relationship between log(variance) and log(time), but the data set used was short, and therefore this result did not really give an indication that the method was valid (1). A later analysis by Schepers et al (23) using four different techniques for examining time series as fractals showed that the method worked apparently well on signals of 8,192 elements or more: the test signals were fractal signals generated by the spectral synthesis method outlined by Saupe, in Peitgen and Saupe (21), the same signal generation method used for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated data, with or without added noise, were fitted using SENSOP, a derivativefree solver with sensitivity scaling for nonlinear least-squares equations (13). The amplitude of the data covered a large range, usually about four orders of magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…Both approaches give equivalent results if the vascular dispersion is set appropriately (ie, approximately 18%) (23). To fit model solutions to the MR tissue contentversus-time curves, a nonlinear least-squares optimizer routine, based on sensitivity functions (24), was used to simultaneously adjust the values of flow and volume for large vessels and microvessels.…”
Section: Mr Blood Flow Estimatesmentioning
confidence: 99%